Evaluation of process parameter of an automated dip-coating - Strobel, Catrin; Kadow-Romacker, Anke; Witascheck, Tom; Schmidmaier, Gerhard; Wildemann, Britt (Materials letters, 2011)
Dip coating is a common technique for the optimization of metallic implants, whereas several steps during the procedure influence the coating. This study aims in the development of a coating apparatus and the evaluation of critical steps, such as mixing, immersion, retention and withdrawal velocity during the procedure. In addition the influence of the polymer solution viscosity, poly(d,l-lactide) dissolved in ethyl acetate, was analyzed. As a therapeutic drug, gentamicin was incorporated and the amount in the different coatings quantified. With increased withdrawal velocity and viscosity the thickness of the coating layer increased. This was accompanied by an increase in incorporated drug. The mixing, immersion and retention time had almost no effect. The viscosity of the polymer solution and the withdrawal velocity can therefore be used to modify bioactive coatings for optimized local drug loading.